2019
DOI: 10.22159/ajpcr.2019.v12i18.34297
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Efficiency of Copper Oxychloride-Conjugated Silver Nanoparticles Against Colletotrichum Gloeosporioides Which Causes Anthracnose Disease

Abstract: Objectives: Anthracnose disease is caused by Colletotrichum gloeosporioides, affecting most of the fruit and vegetable plants. The present study is aimed to synthesize silver nanoparticles (AgNPs) using neem extract and conjugate then with fungicide to check the antifungal activity against anthracnose disease. Methods: In the current study, we have synthesized copper oxychloride-conjugated AgNPs (COC-AgNPs) by a biological method using neem extract and have tested their effectiveness against C. gloeospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…An in-vivo study reported that 0.5% and 1% nanomaterial composite reduced anthracnose disease by 45.7% and 71.3%, respectively [156]. Neem extract was used to synthesize copper oxychlorideconjugated silver (21-25 nm) and treat C. gloeosporioides, resulting in pathogen growth suppression [157].…”
Section: Present and Future Management Of Anthracnosementioning
confidence: 99%
“…An in-vivo study reported that 0.5% and 1% nanomaterial composite reduced anthracnose disease by 45.7% and 71.3%, respectively [156]. Neem extract was used to synthesize copper oxychlorideconjugated silver (21-25 nm) and treat C. gloeosporioides, resulting in pathogen growth suppression [157].…”
Section: Present and Future Management Of Anthracnosementioning
confidence: 99%
“…Copper oxychloride-conjugated silver NPs were synthesized using neem extract and tested for their activity against the causal agent of mango anthracnose (C. gloeosporioides) by [98]. The resulted nonmaterial had spherical shape and an average particle size of 21-25 nm.…”
Section: Mangomentioning
confidence: 99%